Overestimating resistance in field testing of malaria parasites: simple methods for estimating high EC50 values using a Bayesian approach. - Stepniewska, K; Chotivanich, K; Brockman, A; Day, N; White, N (BioMed Central, 2007)
Conventional methods of assessing in-vitro antimalarial drug-concentration effect relationships in field testing of fresh isolates assess each parasite isolate individually. This leads to systematic overestimation of EC50 values for the most resistant isolates, and thus overestimation of the degree of resistance. In antimalarial drug-susceptibility studies conducted on the north-western border of Thailand the overestimation of EC50 for the most resistant isolate ranged from 15% for artesunate to 43% for mefloquine. If isolates cannot be stored for re-testing, more accurate estimations of the degree of resistance can be obtained using a Bayesian approach to data analysis which is described here.